Global burden of chronic kidney disease due to diabetes mellitus type 2 attributable to low physical activity and high body mass index from 1990 to 2021 - Pan, Weifeng; Li, Fangbo; Du, Xiangyu; Ye, Mingyan; Wang, Songtao; Shi, Kexin (Biology of Sport, 2025)
The present study aimed to assess the global chronic kidney disease due to diabetes mellitus type 2 (CKD-T2DM) attributable to low physical activity (PA) and high body-mass index (BMI). Data on CKD-T2DM deaths, disability-adjusted life years (DALYs), and risk factor exposure were obtained from the Global Burden of Disease Study 2021. The jointpoint model was used to detect the temporal patterns throughout the past 32 years, and the age-period-cohort analyses were preformed to clarify the trends in epidemiological shift. The global age standardized rate (ASR) of DALYs for CKD-T2DM linked to low PA were 8.19 (95% UI, 3.21 to 13.60) per 100,000 people. No significant percent changes were observed since 1990. Globally, high BMI accounted for 50.14 (95% UI, 22.56 to 79.15) ASR of DALYs with a marked increase of 62.66 %(95 % UI, 44.24 to 78.73) from 1990. Both low PA and high BMI attributable CKD-T2DM showed a surging trend in population aged less than 40 or greater than 75. There were consistent nonlinear trajectories between socio-demographic index (SDI) and CKD-T2DM attributable to low PA and high BMI, which reached a peak at SDI = 0.6 before decreasing with a higher SDI value. Globally, there are rising trends in CKD-T2DM burden, low PA exposure, and high BMI exposure until 2050. There are secular improvements in CKD T2DM attributable to low PA, while it remains a severe challenge in that of high BMI. Considerable temporal and regional variation highlight the urgency of structural, context specific strategies targeted on modifiable factors to tackle the CKD-T2DM burden.